The anatomy of peace resolving the heart of conflict (Berrett-Koehler Publishers, Inc., a BK Life book, 2015)
Like Leadership and Self-Deception, The Arbinger Institute's first book, The Anatomy of Peace has become a worldwide phenomenon - not because of a media blitz, movie tie-in, or celebrity endorsement, but because readers have enthusiastically recommended it to colleagues, relatives, and friends. The Anatomy of Peace asks, What if conflicts at home, conflicts at work, and conflicts in the world stem from the same root cause? What if we systematically misunderstand that cause? And what if, as a result, we unwittingly perpetuate the very problems we think we are trying to solve? Through an intriguing story we learn how and why we contribute to the divisions and problems we blame on others and the surprising way that these problems can be solved. Yusuf al-Falah, an Arab, and Avi Rozen, a Jew, each lost his father at the hands of the other's ethnic cousins. The Anatomy of Peace is the story of how they came together, how they help warring parents and children come together, and how we too can find our way out of the struggles that weigh us down. This second edition includes new sections enabling readers to go deeper into the book's key concepts, access to free digital study and discussion guides, and information about The Reconciliation Project, a highly successful global peace initiative based on concepts in The Anatomy of Peace.